A self-supporting carbon-based material loaded with iron nanoparticles and its preparation method and application

By combining iron with carbon-based materials, a self-supported carbon-based material is formed with the self-supported carbon-based material of loaded iron nanoparticles, the problems of poor ammonia selectivity and high energy consumption in electrocatalytic methods are solved, and efficient removal and conversion of nitrates are achieved, with stability and wide adaptability.

CN119456003BActive Publication Date: 2025-04-18TONGJI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510051940.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-18
Estimated Expiration
2045-01-14

AI Technical Summary

Technical Problem

The existing electrocatalytic methods have poor selectivity of ammonia during nitrate reduction, requiring a high overpotential, resulting in large energy consumption, and nanostructured iron-based catalysts are prone to aggregation, oxidation, corrosion, and poor chemical stability.

Method used

By combining iron with carbon-based materials with good conductivity and pore structure, a self-supporting carbon-based material is formed by combining iron nanoparticles. The material is synthesized by hydrothermal method to uniformly disperse the iron nanoparticles, inhibit their agglomeration, and promote catalytic reactions through the electron gain and loss process of Fe species.

Benefits of technology

It realizes efficient removal and conversion of nitrates in water, has high removal rate, selectivity and stability, has a wide range of application, and can reduce the energy consumption of industrial ammonia production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119456003B_ABST
    Figure CN119456003B_ABST
Patent Text Reader

Abstract

The present invention provides a self-supporting carbon-based material loaded with iron nanoparticles, and a preparation method and application thereof, and belongs to the technical field of preparation and application of electrocatalysts for removing nitrates from sewage. The preparation method of the self-supporting carbon-based material loaded with iron nanoparticles of the present invention comprises: providing a carbon felt that has been acid-washed and heated in a water bath; mixing an iron precursor and urea in a solvent to obtain a mixed solution containing iron salts; mixing the carbon felt with the mixed solution containing iron salts and performing a hydrothermal reaction to obtain the self-supporting carbon-based material loaded with iron nanoparticles. When the self-supporting carbon-based material loaded with iron nanoparticles provided by the present invention is used as a cathode to electrocatalyze nitrate-containing wastewater, it has a good removal rate and ammonia nitrogen selectivity. Under acidic, neutral, alkaline conditions and different initial nitrate concentrations, the catalyst can maintain a high effect of removing nitrate nitrogen and producing ammonia nitrogen, and has the advantages of high removal efficiency, good ammonia nitrogen selectivity, and strong stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation and application of an electrocatalyst for removing nitrate from sewage, and in particular to a self-supporting carbon-based material loaded with iron nanoparticles and a preparation method and application thereof. Background Art

[0002] At present, the main methods for treating nitrates include physical, chemical and biological treatment methods such as ion exchange, reverse osmosis, electrodialysis, and biological denitrification, but they all have disadvantages such as complex processes, high costs, and secondary pollution. In recent years, electrocatalytic nitrate reduction has gradually become a research focus, which has the advantages of being green and clean, not requiring the consumption of reducing agents, controllable reaction products, high efficiency and low cost. Through the rational design of electrocatalysts, pollutant nitrates can also be converted into valuable chemicals such as ammonia, which is expected to become an alternative to the high-temperature, high-pressure, and high-energy Haber process.

[0003] However, the electrocatalytic method has the problem of poor selectivity for ammonia due to the presence of multiple electron / proton transfer steps. A high overpotential is required to achieve a high ammonia yield, which consumes a lot of energy. The key to solving this problem is the design of the electrocatalyst. Among various electrocatalysts, transition metals have the advantages of being abundant in the earth's crust and low in cost. Among them, iron is the most widely present transition metal element in nature. It is not only low in cost and non-toxic, but also exists in almost all nitrogenases and plays an important role as the active center in the electron transfer process. The iron-based catalyst prepared also shows high removal efficiency and selectivity in nitrate reduction. However, nanostructured iron-based catalysts with natural magnetism and high surface energy are prone to aggregation, and also have disadvantages such as easy oxidation, easy corrosion, and poor chemical stability, which leads to a reduction in active sites. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a self-supporting carbon-based material loaded with iron nanoparticles, and a preparation method and application thereof. The electrocatalytic material obtained by the present invention has the advantages of high electrocatalytic removal rate of nitrates, good selectivity, good stability, etc. The present invention combines iron with a carbon-based material with good conductivity and pore structure to form a composite material that can evenly disperse the iron-based material, effectively inhibit the agglomeration of iron particles, and at the same time produce a synergistic effect, improve the catalytic activity of the material, and ultimately achieve efficient removal and conversion of nitrates in water.

[0005] The first object of the present invention is to provide a method for preparing a self-supporting carbon-based material loaded with iron nanoparticles, comprising the following steps:

[0006] Providing a carbon felt after being acid-soaked and water-bath heated;

[0007] Mixing an iron precursor and urea in a solvent to obtain a mixed solution containing an iron salt;

[0008] The carbon felt is mixed with the mixed solution containing the iron salt and subjected to a hydrothermal reaction to obtain the self-supporting carbon-based material loaded with iron nanoparticles.

[0009] In the present invention, urea is used as an N dopant to provide an alkaline environment; the decomposition products and coordination behavior of urea can play a role in constructing material morphology structures such as pore structure and stratification, and can adjust the morphology of the material; and change the crystal morphology and structure of the material.

[0010] In some embodiments of the present invention, the acid is selected from concentrated sulfuric acid and / or nitric acid, and the concentration of the acid is 30 wt %. The method further includes drying the carbon felt at a drying temperature of 60°C.

[0011] In some embodiments of the present invention, the water bath heating temperature is 50-100° C. and the time is 2-8 h.

[0012] In some embodiments of the present invention, the iron precursor is selected from ferrous sulfate heptahydrate and / or ferrous chloride tetrahydrate.

[0013] In some embodiments of the present invention, the molar ratio of the iron precursor to urea is (0.5:8) to (2:8).

[0014] In some embodiments of the present invention, the mixed solution containing the iron salt is further stirred using a magnetic stirrer, the rotation speed is maintained at 200 r / min to 300 r / min, and the stirring is performed for 5 to 30 min until the solution is uniformly mixed.

[0015] In some embodiments of the present invention, the conditions of the hydrothermal reaction are: reaction temperature is 100-120°C-110°C, and reaction time is 6-10 h.

[0016] The second object of the present invention is to provide a self-supporting carbon-based material loaded with iron nanoparticles, wherein the self-supporting carbon-based material loaded with iron nanoparticles uses carbon felt as a carrier, the iron nanoparticles are uniformly dispersed on the surface of the carrier, and the iron nanoparticles have a layered structure.

[0017] In some embodiments of the present invention, the loading amount of the iron nanoparticles is 1 wt%~3 wt%.

[0018] The third object of the present invention is to provide the use of the self-supporting carbon-based material loaded with iron nanoparticles in the electrocatalytic treatment of nitrates in nitrogen-containing wastewater.

[0019] In some embodiments of the present invention, the concentration of nitrate nitrogen in the nitrate-containing wastewater is 50 mg-N / L to 300 mg-N / L.

[0020] In some embodiments of the present invention, the pH of the electrocatalytic reaction is 3-12.

[0021] In some embodiments of the present invention, the self-supporting carbon-based material loaded with iron nanoparticles is used as a working electrode, a platinum sheet electrode is used as a counter electrode, and a saturated calomel electrode is used as a reference electrode in electrocatalysis to form a three-electrode system in an H-type electrolytic cell separated by a Nafion-117 proton exchange membrane.

[0022] In some embodiments of the present invention, the electrocatalytic reaction time is 2 to 22 h.

[0023] In some embodiments of the present invention, the voltage of the working electrode is -1.5~-1.2V vs. SCE.

[0024] The above technical solution of the present invention has the following advantages compared with the prior art:

[0025] The present invention provides a preparation method and application method of a self-supporting carbon-based material loaded with iron nanoparticles as an electrocatalyst for removing nitrates from sewage. The synthesis method is simple, and the raw materials are inexpensive and environmentally friendly. The self-supporting carbon-based material loaded with iron nanoparticles synthesized by the hydrothermal method provided by the present invention uses a carbon felt material as a carrier of the active component, which helps to disperse the iron nanoparticles and improve the defects of the iron nanoparticles that are easy to aggregate and unstable; the iron-based nanoparticles can be directly grown on the carbon substrate without the need for a binder, which can reduce the resistivity and effectively prevent the active components from falling off, thereby improving the catalytic activity and stability of the material. Studies have shown that NO3 on iron-based catalysts - Converted to NO2 - It is the rate-determining step (RDS) in the nitrate reduction process, which limits the kinetic rate of the overall reaction. In the nitrate reduction process of the present invention, the divalent iron Fe(II) in the material can act as an electron donor, and the electrons quickly remove the NO3 adsorbed on the cathode surface. - Reduction to intermediate NO2 - , Fe(Ⅱ) loses electrons and becomes Fe(Ⅲ) intermediate. Subsequently, Fe(Ⅲ) can obtain electrons at the cathode and be converted into Fe(Ⅱ) to achieve catalyst regeneration.

[0026] In summary, the iron-based catalyst of the present invention can promote the transfer of electrons through the electron gain and loss process of Fe species, accelerate the kinetics of RDS, and thus facilitate the NO3 -Converted into NH3. The results of the embodiments show that when the self-supporting carbon-based material with loaded iron nanoparticles synthesized by the hydrothermal method provided by the present invention is used as an electrocatalyst for electrocatalytic reduction of nitrate, it can maintain a high effect of removing nitrate nitrogen and producing ammonia nitrogen under acidic, neutral, alkaline and different initial nitrate concentration conditions, and has the advantages of high removal efficiency, good selectivity, wide application range and strong stability. It can not only eliminate nitrate pollution in water bodies, but also prepare ammonia, which is expected to solve the defect of energy consumption in industrial ammonia production.

[0027] The present invention combines iron with a carbon-based material having good electrical conductivity and pore structure to form a composite material that can evenly disperse the iron-based material and prevent iron particles from agglomerating. At the same time, it can also produce a synergistic effect, improve the catalytic activity of the material, and ultimately achieve efficient removal and conversion of nitrates in water. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific embodiments of the present invention in conjunction with the accompanying drawings, wherein:

[0029] Figure 1 These are SEM images of the self-supporting carbon-based material (FeCO3NPs-1@CF) loaded with iron nanoparticles in Example 1 of the present invention. Among them, (a)-(b) are pure carbon felt; (c)-(d) are SEM images of FeCO3NPs-1@CF.

[0030] Figure 2 This is an elemental dimensional distribution spectrum image (Mapping) of the self-supporting carbon-based material (FeCO3NPs-1@CF) loaded with iron nanoparticles in Example 1 of the present invention.

[0031] Figure 3 This is the XRD spectrum of the self-supporting carbon-based material loaded with iron nanoparticles (FeCO3NPs-1@CF) in Example 1 of the present invention.

[0032] Figure 4 This is the XPS full spectrum image and Fe 2p orbital spectrum of the self-supporting carbon-based material loaded with iron nanoparticles (FeCO3NPs-1@CF) in Example 1 of the present invention.

[0033] Figure 5 This is a SEM image of the self-supporting carbon-based material (FeCO3NPs-Cl@CF) loaded with iron nanoparticles in Comparative Example 1 of the present invention.

[0034] Figure 6It is the removal rate of the simulated nitrate wastewater by the self-supporting carbon-based material FeCO3HYPERLINK"mailto:NPs-x@CF(x=0.5" NPs-x@CF(x=0.5, 1, 1.5, 2) loaded with iron nanoparticles in Example 1 of the present invention; wherein, (a) is the product selectivity and nitrate removal rate, and (b) is the ammonia yield and Faraday efficiency.

[0035] Figure 7 It is the removal rate of the simulated nitrate wastewater by the materials in Example 1 of the present invention and Comparative Example 1, wherein (a) is the product selectivity and nitrate removal rate, and (b) is the ammonia yield and Faraday efficiency.

[0036] Figure 8 The removal rate of FeCO3NPs-1@CF, a self-supporting carbon-based material loaded with iron nanoparticles, for simulated nitrate wastewater with different initial pH values ​​in Example 1 of the present invention; wherein (a) is the product selectivity and nitrate removal rate, and (b) is the ammonia yield and Faraday efficiency.

[0037] Fig. 9 The removal rate of FeCO3NPs-1@CF, a self-supporting carbon-based material loaded with iron nanoparticles, for simulated nitrate wastewater with different initial concentrations in Example 1 of the present invention; wherein (a) is the product selectivity and nitrate removal rate and (b) is the ammonia yield and Faraday efficiency.

[0038] Fig.10 The nitrate removal rate and product selectivity of the self-supporting carbon-based material FeCO3NPs-1@CF loaded with iron nanoparticles in Example 1 of the present invention were obtained by 11 consecutive electrocatalytic experiments. DETAILED DESCRIPTION

[0039] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.

[0040] Example 1

[0041] This embodiment provides a self-supporting carbon-based material loaded with iron nanoparticles and a preparation method thereof. The method of this embodiment comprises the following steps:

[0042] (1) Soak the carbon felt in a 30 wt% nitric acid solution, heat it to 60 °C in a water bath and keep it for 6 h, rinse it with deionized water several times, and then put it in a vacuum drying oven at 60 °C for 12 h for later use;

[0043] (2) Take 0.5 mmol, 1 mmol, 1.5 mmol, and 2 mmol of FeSO4·7H2O and 8 mmol of urea, respectively, and put them into a beaker. Add 15 ml of deionized water and stir with a magnetic stirrer at a speed of 200 r / min to 300 r / min. Stir for 20 min to mix the solution evenly and set aside to obtain a mixed solution.

[0044] (3) Cut the carbon felt pretreated in step (1) into a size of 2 cm × 2 cm, put it into a reactor with the mixed solution obtained in step (2), set the temperature to 110 °C, and perform hydrothermal reaction for 8 h;

[0045] (4) The material after the hydrothermal reaction in step (3) was taken out, rinsed with ethanol and distilled water several times, and then placed in a vacuum drying oven at 60 °C for 12 h, and finally obtained self-supporting carbon-based materials with different loading ratios of iron nanoparticles (FeCO3 HYPERLINK"mailto:NPs-x@CF, x=0.5" NPs-x@CF, x=0.5, 1, 1.5, 2). The obtained self-supporting carbon-based material FeCO3NPs-1@CF loaded with iron nanoparticles was structurally characterized, and the results are shown in Fig. Figures 1 to 4 ,Depend on Figure 1 It can be seen that the surface of pure carbon felt is smooth, while the obtained self-supporting carbon-based material loaded with iron nanoparticles has a stacked layered structure, indicating that the iron nanoparticles are successfully loaded on the carbon felt; Figure 2 It can be seen that the C element is widely distributed, forming the basic framework of the material and serving as the carrier of the iron nano-active component. The Fe and O elements are distributed clearly and evenly in the region, indicating the successful loading of the active component. Figure 3 It can be seen that FeCO3 is the main substance in the synthetic material; Figure 4 The XPS full spectrum scan shows that there are three elements, Fe, C and O, on the surface of the prepared materials. The XPS spectrum of Fe 2p orbital proves that Fe 2+ and a small amount of Fe 3+ existence.

[0046] Comparative Example 1

[0047] This comparative example provides a self-supporting carbon-based material loaded with iron nanoparticles and a preparation method thereof. The method of this comparative example comprises the following steps:

[0048] (1) Soak the carbon felt in a 30 wt% nitric acid solution, heat it to 60 °C in a water bath and keep it for 6 h, rinse it with deionized water several times, and then put it in a vacuum drying oven at 60 °C for 12 h for later use;

[0049] (2) Take 1 mmol of FeCl2·4H2O and 8 mmol of urea and put them into a beaker. Add 15 ml of deionized water and stir with a magnetic stirrer at a speed of 200 r / min to 300 r / min. Stir for 20 min to mix the solution evenly and set aside to obtain a mixed solution.

[0050] (3) Cut the carbon felt pretreated in step (1) into a size of 2 cm × 2 cm, put it into a reactor with the mixed solution obtained in step (2), set the temperature to 110 °C, and perform hydrothermal reaction for 8 h;

[0051] (4) The material after the hydrothermal reaction in step (3) was taken out, rinsed with ethanol and distilled water several times, and then placed in a vacuum drying oven at 60 °C for 12 h to finally obtain a self-supporting carbon-based material loaded with iron nanoparticles (FeCO3NPs-Cl@CF). The obtained self-supporting carbon-based material loaded with iron nanoparticles was characterized by SEM. The results are shown in Figure 5 .Depend on Figure 5 It can be seen that the obtained FeCO3NPs-Cl@CF material is composed of numerous irregular small block particles tightly stacked together, without an obvious layered structure, indicating that the morphology of the material has changed after changing the type of iron precursor.

[0052] Performance Testing

[0053] 1. Application of FeCO3NPs-x@CF self-supporting carbon-based materials loaded with iron nanoparticles in different proportions obtained in Example 1 in treating nitrate in nitrogen-containing wastewater comprises the following steps:

[0054] A 1 cm×2 cm FeCO3NPs-x@CF self-supporting carbon-based material was used as a working electrode, a 1 cm×1 cm platinum sheet electrode was used as a counter electrode, and a saturated calomel electrode was used as a reference electrode. A three-electrode system was formed in an H-type electrolytic cell separated by a Nafion-117 proton exchange membrane. 25 mL of nitrogen-containing wastewater with a nitrate concentration of 100 mg-N / L was added to the cathode chamber of the H-type electrolytic cell. The content of Na2SO4 in the nitrogen-containing wastewater was 0.1 mol / L. The voltage of the working electrode was -1.3 V vs. SCE. The electrocatalytic denitrification reaction was carried out at room temperature for 2 h, and then the nitrate removal rate, ammonia nitrogen selectivity, ammonia yield and Faraday efficiency were measured. The results are shown in Figure 2. Figure 6 shown.

[0055] Depend on Figure 6It can be seen that, in comparison, the FeCO3NPs-1@CF material prepared with an iron precursor dosage of 1 mmol has the highest nitrate removal rate (98.46%), ammonia selectivity (96.06%) and Faraday efficiency (79.13%). The ammonia yield is also significantly higher than that of materials prepared with other iron dosages. Overall, it has better electrocatalytic activity and is suitable as a cathode material for electrocatalytic reduction of nitrate.

[0056] 2. Application of the self-supporting carbon-based material loaded with iron nanoparticles obtained in Example 1 and Comparative Example 1 in treating nitrate in nitrogen-containing wastewater comprises the following steps:

[0057] 1 cm×2 cm self-supporting carbon-based materials FeCO3NPs-1@CF and FeCO3NPs-Cl@CF were used as working electrodes, 1 cm×1 cm platinum sheet electrode was used as counter electrode, and saturated calomel electrode was used as reference electrode to form a three-electrode system in an H-type electrolytic cell separated by a Nafion-117 proton exchange membrane. 25 mL of nitrogen-containing wastewater with a nitrate concentration of 100 mg-N / L was added to the cathode chamber of the H-type electrolytic cell. The content of Na2SO4 in the nitrogen-containing wastewater was 0.1 mol / L. The voltage of the working electrode was -1.3 V vs. SCE. The electrocatalytic denitrification reaction was carried out at room temperature for 2 h, and then the nitrate removal rate, ammonia nitrogen selectivity, ammonia yield and Faraday efficiency were measured. The results are shown in Figure 7 shown.

[0058] Depend on Figure 7 It can be seen that after 2 h of electrocatalytic reaction, compared with the FeCO3NPs-Cl@CF material prepared with FeCl2·4H2O as the iron precursor, the FeCO3NPs-1@CF material prepared with 1 mmol FeSO4·7H2O as the iron precursor has a higher nitrate removal rate, ammonia selectivity and ammonia yield, has better electrochemical performance, and is more suitable as a cathode material for electrocatalytic reduction of nitrate.

[0059] 3. Application of the self-supporting carbon-based material FeCO3NPs-1@CF loaded with iron nanoparticles obtained in Example 1 in treating nitrate in nitrogen-containing wastewater with different initial pH values ​​comprises the following steps:

[0060] A 1 cm×2 cm FeCO3NPs-1@CF self-supporting carbon-based material was used as a working electrode, a 1 cm×1 cm platinum sheet electrode was used as a counter electrode, and a saturated calomel electrode was used as a reference electrode. A three-electrode system was formed in an H-type electrolytic cell separated by a Nafion-117 proton exchange membrane. 25 mL of nitrogen-containing wastewater with a nitrate concentration of 100 mg-N / L was added to the cathode chamber of the H-type electrolytic cell. The content of Na2SO4 in the nitrogen-containing wastewater was 0.1 mol / L. The voltage of the working electrode was -1.3 V vs. SCE. The initial pH of the cathode electrolyte was adjusted to 3, 5, 7, 9, and 12 with H2SO4 or NaOH solution, respectively. The electrocatalytic denitrification reaction was carried out at room temperature for 2 h, and then the nitrate removal rate, ammonia nitrogen selectivity, ammonia yield and Faraday efficiency were measured. The results are shown in Figure 2. Figure 8 shown.

[0061] Depend on Figure 8 It can be seen that, in general, after 2h of electrocatalytic reaction, the FeCO3NPs-1@CF material has a nitrate removal efficiency and ammonia selectivity of more than 85% at pH 3-12, indicating that the material has strong adaptability to pH and can perform electrocatalytic reactions in a relatively wide pH range.

[0062] 4. Application of the nitrogen-doped mesoporous carbon-based nanomaterial loaded with iron nanoparticles self-supporting carbon-based material obtained in Example 1 in treating nitrogen-containing wastewater with different initial nitrate concentrations comprises the following steps:

[0063] A 1 cm×2 cm FeCO3NPs-1@CF self-supporting carbon-based material was used as the working electrode, a 1 cm×1 cm platinum sheet electrode was used as the counter electrode, and a saturated calomel electrode was used as the reference electrode. A three-electrode system was formed in an H-type electrolytic cell separated by a Nafion-117 proton exchange membrane. 25 mL of nitrogen-containing wastewater with nitrate concentrations of 50 mg-N / L, 100 mg-N / L, 200 mg-N / L, 300 mg-N / L and 500 mg-N / L was added to the cathode chamber of the H-type electrolytic cell. The content of Na2SO4 in the nitrogen-containing wastewater was 0.1 mol / L, the initial pH of the electrolyte was 7, and the voltage of the working electrode was -1.3 Vvs. SCE. The electrocatalytic denitrification reaction was carried out at room temperature for 2 h, and then the nitrate removal rate, ammonia nitrogen selectivity, ammonia yield and Faraday efficiency were measured. The results are shown in Figure 2. Fig. 9 shown.

[0064] Depend on Fig. 9 It can be seen that the FeCO3NPs-1@CF material has good performance at low initial nitrate concentration (≤200 mg-N L -1) has a higher ammonia selectivity, and with the increase of initial nitrate concentration, the ammonia yield and Faradaic efficiency show a trend of first increasing and then decreasing. -1 After that, the nitrate removal efficiency of the material decreased because high concentrations of nitrate may occupy the active area on the catalyst surface, thereby weakening its catalytic effect.

[0065] 5. The stability and durability of the nitrogen-doped mesoporous carbon-based nanomaterial loaded with iron nanoparticles self-supporting carbon-based material obtained in Example 1 in the electrocatalytic reaction include the following steps:

[0066] S5: A 1 cm×2 cm FeCO3NPs-1@CF self-supporting carbon-based material was used as the working electrode, a 1 cm×1 cm platinum sheet electrode was used as the counter electrode, and a saturated calomel electrode was used as the reference electrode. A three-electrode system was formed in an H-type electrolytic cell separated by a Nafion-117 proton exchange membrane. 25 mL of nitrogen-containing wastewater with a nitrate concentration of 100 mg-N / L was added to the cathode chamber of the H-type electrolytic cell. The content of Na2SO4 in the nitrogen-containing wastewater was 0.1 mol / L, the initial pH of the electrolyte was 7, and the voltage of the working electrode was -1.3 V vs. SCE. The electrocatalytic denitrification reaction was carried out at room temperature for 2 h. After each cycle experiment, the electrolyte was replaced, and the electrode material was rinsed with deionized water and dried naturally, and then used for the following experiment. A total of 11 cycles were tested.

[0067] Depend on Fig.10 It can be seen that the nitrate removal rate and ammonia selectivity of FeCO3NPs-1@CF as an electrode can be maintained above 80% in 11 cycles of electrocatalytic experiments, which shows that the material has a relatively stable catalytic effect, can realize multiple cycles of electrode use, and has practical application feasibility.

[0068] Obviously, the above embodiments are merely examples for clear explanation and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from these are still within the protection scope of the invention.

Claims

1. Application of a self-supporting carbon-based material loaded with iron nanoparticles in electrocatalytic treatment of nitrate in nitrogen-containing wastewater; the self-supporting carbon-based material loaded with iron nanoparticles uses carbon felt as a carrier, the iron nanoparticles are uniformly dispersed on the surface of the carrier, the iron nanoparticles have a layered structure, and the iron nanoparticles are FeCO3; the preparation method of the self-supporting carbon-based material loaded with iron nanoparticles comprises the following steps: Providing a carbon felt that has been acid washed and water bath heated; Mixing ferrous sulfate heptahydrate and urea in a solvent to obtain a mixed solution containing iron salt; The carbon felt is mixed with the mixed solution containing the iron salt and subjected to a hydrothermal reaction to obtain the self-supporting carbon-based material loaded with iron nanoparticles.

2. The use according to claim 1, characterized in that: The acid is selected from nitric acid and / or concentrated sulfuric acid; The water bath heating temperature is 50-100°C and the heating time is 2-8 h.

3. The use according to claim 1, characterized in that: The molar ratio of the ferrous sulfate heptahydrate to urea is (0.5:8) to (2:8).

4. The use according to claim 1, characterized in that: The conditions of the hydrothermal reaction are: reaction temperature is 100-120° C., and reaction time is 6-10 h.

5. The use according to claim 1, characterized in that: The loading amount of the iron nanoparticles is 1 wt% to 3 wt%.

6. The use according to claim 1, characterized in that: The concentration of nitrate nitrogen in the nitrate-containing wastewater is 50 mg-N / L to 300 mg-N / L.

7. The use according to claim 1, characterized in that: The pH of the electrocatalytic reaction is 3~12.